Accounting for means of individualization of modern enterprise: problems and improvement directions - K.I. Skop (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The research describes the existing methodology of accounting for the means of individualization of a modern enterprise, within which they are not recognized as intangible assets and are not subject to reporting. The article deals with the peculiarities of the legal nature of the commercial name, the geographical indication and trademark that influence upon the process of their accounting. The necessity of registering geographical indication and trademark as intangible assets is substantiated and the features of determination of their useful life in accounting are disclosed. The factors influencing on the value of the trademark are presented and the relevance of the accounting method for the revalued value is specified.